Minimum Degree Thresholds for Hamilton (K/2)-Cycles in K-Uniform Hypergraphs - Han, H (Academic Press, 2022)
For any even integer k≥6, integer d such that k/2≤d≤k−1, and sufficiently large n∈(k/2)N, we find a tight minimum d-degree condition that guarantees the existence of a Hamilton (k/2)-cycle in every k-uniform hypergraph on n vertices. When n∈kN, the degree condition coincides with the one for the existence of perfect matchings provided by Rödl, Ruciński and Szemerédi (for d=k−1) and Treglown and Zhao (for d≥k/2), and thus our result strengthens theirs in this case. © 2021 Elsevier Inc.
Keywords: Hamilton cycle; Hypergraph; Absorbing method; Regularity lemma